On the sub-micron aerosol size distribution in a coastal-rural site at El Arenosillo Station (SW – Spain) - Sorribas, Mar (2011)
Abstract. This study focuses on the analysis of the submicron aerosol characteristics at El Arenosillo Station, a rural and coastal environment in South-western Spain between 1 August 2004 and 31 July 2006 (594 days). The mean total concentration (NT) was 8660 cm−3 and the mean concentrations in the nucleation (NNUC ), Aitken (NAIT ) and accumulation (NACC ) particle size ranges were 2830 cm−3 , 4110 cm−3 and 1720 cm−3 , respectively. Median size distribution was characterised by a single-modal fit, with a geometric diameter, median number concentration and geometric standard deviation of 60 nm, 5390 cm−3 and 2.31, respectively. Characterisation of primary emissions, secondary particle formation, changes to meteorology and long-term transport has been necessary to understand the seasonal and annual variability of the total and modal particle concentration. Number concentrations exhibited a diurnal pattern with maximum concentrations around noon. This was governed by the concentrations of the nucleation and Aitken modes during the warm seasons and only by the nucleation mode during the cold seasons. Similar monthly mean total concentrations were observed throughout the year due to a clear inverse variation between the monthly mean NNUC and NACC . It was related to the impact of desert dust and continental air masses on the monthly mean particle levels. These air masses were associated with high values of NACC which suppressed the new particle formation (decreasing NNUC ). Each day was classified according to a land breeze flow or a synoptic pattern influence. The median size distribution for desert dust and continental aerosol was dominated by the Aitken and accumulation modes, and marine air masses were dominated by the nucleation and Aitken modes. Particles moved off-shore due to the land breeze and had an impact on the particle burden at noon, especially when the wind was blowing from the NW sector in the morning during summer time. This increased NNUC and NAIT by factors of 3.1 and 2.4, respectively. Nucleation events with the typical “banana” shape were characterised by a mean particle nucleation rate of 0.74 cm−3 s−1 , a mean growth rate of 1.96 nm h−1 and a mean total duration of 9.25 h (starting at 10:55 GMT and ending at 20:10 GMT). They were observed for 48 days. Other nucleation events were identified as those produced by the emissions from the industrial areas located at a distance of 35 km. They were observed for 42 days. Both nucleation events were strongly linked to the marine air mass origin.